Control Programs of tuberculosis from 1963 to 1970 in Cuba. Historic analysis - Enrique Ramón Beldarraín Chaple (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
The fight against tuberculosis began in Cuba at the end of the XIX century, in Santiago de Cuba. At the beginning of the XX century the League Against Tuberculosis was created with a limited action for the lack of funds and an adequated strategy. In 1936 The National Board of tuberculosis was created, that accomplished few activities and they did not cause impact neither in morbidity nor in mortality produced by the disease in the population. In 1959, with the change of strategy introduced by the State Public Health Department, directed fundamentally toward the promotional activities and prevention of health, the Tuberculosis's department was organized, that established and directed the Program of Control of Tuberculosis for the first time in Cuba in 1963, completely renewed in 1970. This work has the purpose to describe and systematize the principal experiences of the First Program of Control of Tuberculosis (1963), doing a historical analysis of the elements and actions that were introduced like changes in the version of the Program of Control of 1970 and its repercussion in the subsequent evolution of the disease in Cuba.